Heat stress does not exacerbate tennis-induced alterations in physical performance - Girard, O.; Christian, R. J.; Racinais, S.; Périard, J. D. (British Journal of Sports Medicine, 2014)
Objectives To assess the time course of changes in physical performance in response to match-play tennis under heat stress. Methods: Two matches consisting of 20 min of effective playing time (2×10 min segments) were played in COOL (~102 min; ~22°C and 70% relative humidity (RH)) and HOT (~119 min; ~36°C and 35% RH) environments. Repeated-sprint ability (3×15 m, 15 s rest), 15 m sprint time with a direction change (180°), vertical jump height (squat and countermovement jumps) and leg stiffness (multirebound jumps) were assessed in 12 competitive male players prematch, midmatch and postmatch, and 24 and 48 h after match completion.Results During the repeated-sprint ability test, initial (+2.3% and +3.1%) and cumulated sprint (+1.5% and +2.8%) times increased from prematch to midmatch and postmatch, respectively (p<0.001), while the sprint decrement score did not change. Match-play tennis induced a slowing (average of both conditions: +1.1% and +1.3% at midmatch and postmatch time points; p=0.05) of 15 m sprint time with direction change. Compared with prematch, leg stiffness (-6.4% and -6.5%; p<0.001) and squat jump height (-1.5% and -2.4%; p=0.05), but not countermovement jump height (-0.7% and -1.3%; p>0.05), decreased midmatch and postmatch, respectively, regardless of the condition. Complete recovery in all physical performance markers occurred within 24 h. Conclusions: In tennis, match-related fatigue is characterised by impaired repeated-sprint ability, explosive power and leg stiffness at midmatch and postmatch, with values restored to prematch baseline 24 h into recovery. In addition, physical performance responses (match and recovery kinetics) are identical when competing in cool and hot environments.